1989
DOI: 10.1104/pp.90.3.996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 5-Aminolevulinic Acid Synthesis in Developing Chloroplasts

Abstract: Intact chloroplasts isolated from greening cucumber (Cucumis sativus L. var Beit Alpha) cotyledons regenerated protochlorophyllide (Pchlide) in the dark with added cofactors from either exogenous glutamate or endogenous substrates. No other intermediates of the chlorophyll biosynthetic pathway accumulated. When inhibitors of 5-aminolevulinic acid (ALA) dehydratase were added, the Pchlide that failed to form was replaced by an excessive amount of ALA. When greening seedlings were retumed to the dark, ALA-synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…During the dark cycle the MV Pchlide levels initially increased at the same rate for a11 three plants. However, the wild-type MV Pchlide pool leveled off sooner, at about 1700 pmol g-' fresh weight, a value previously reported in the literature for cucumbers (Huang and Castelfranco, 1989), whereas the mutant levels continued to increase. When the time-course experiment was extended for an additional 8 h (shaded area) to determine whether the Pchlide level in the mutants might also level off, it was found that the mutant MV Pchlide content still continued to increase.…”
Section: Precursor Pools In the Chl Synthesis Pathwaymentioning
confidence: 62%
See 1 more Smart Citation
“…During the dark cycle the MV Pchlide levels initially increased at the same rate for a11 three plants. However, the wild-type MV Pchlide pool leveled off sooner, at about 1700 pmol g-' fresh weight, a value previously reported in the literature for cucumbers (Huang and Castelfranco, 1989), whereas the mutant levels continued to increase. When the time-course experiment was extended for an additional 8 h (shaded area) to determine whether the Pchlide level in the mutants might also level off, it was found that the mutant MV Pchlide content still continued to increase.…”
Section: Precursor Pools In the Chl Synthesis Pathwaymentioning
confidence: 62%
“…Altematively, although the pathway is clearly blocked during both day and night, the block could be more extensive during the daytime. Thus, the mutations could be affecting the regulation of the enzyme's activity, or possibly the mutations could indirectly perturb the phytochrome-dependent mechanism (Huang and Castelfranco, 1989) that shuts off ALA synthesis at night, which involves heme and the products of the tigrina loci (in barley) (reviewed by Somerville, 1986). Clearly, these results will be more easily addressed in the future when both the Mg-chelatase and the nature of these mutants are defined at the molecular level.…”
Section: Pchlide Accumulation In the Mutantsmentioning
confidence: 99%
“…The decline and recovery were complete in approximately 50 min (12). In the present study, the light-mediated in vivo restoration of the ALA-synthesizing capacity has been further examined.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously observed (12) that ALA-synthesizing capacity in isolated chloroplasts greatly declines when etiolated cucumber seedlings that have been exposed to white light (60 ME.-m2 s') for 20 h are returned to the dark, and largely recovers when the dark-treated seedlings are again exposed to continuous white light (12). The decline and recovery were complete in approximately 50 min (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation